Penerapan Akuntansi Pada Usaha Mikro Kecil dan Menengah (UMKM) - Wardokhi Wardokhi; Ngatimin Ngatimin; Hidayatul Muarifin (Prisani Cendekia, 2023)
This research was conducted on MSME actors on Jln. Using a descriptive qualitative research type, Surya Kencana Pamulang, South Tangerang, Banten Province. The type of data used is primary data. In addition, in this study, a survey technique was used using a questionnaire. The analysis technique of this research is a qualitative descriptive analysis technique. The results of this study concluded that MSME actors on Jln. Surya Kencana Pamulang, South Tangerang, Banten Province, has recorded the results of daily sales, purchases of raw materials (inventory), daily expenses, and payroll for those who have employees, but accounting standards have not been met because they are still in the form of simple records. The obstacle SMEs face in applying for accounting is due to their educational background, most of which are junior high schools, some are vocational schools, but their knowledge of accounting still needs to be improved and also because there is no need for the application of accounting